On the Verge of Collapse: Representation of British and Irish Identity in J.G. Farrell’s Troubles - TURAN, AYŞEGÜL (Atatürk Üniversitesi Edebiyat Fakültesi, 2020)
This article aims to examine the juxtaposition of individual stories and collective history in J.G. Farrell’s Troubles to present a nuanced reading of identity politics in Ireland during the Irish War of Independence. Farrell’s the Lost Man Booker Prize recipient novel portrays one of the most tumultuous periods of Irish history (1919-1922) focusing on the daily lives of characters rather than the major political actors of the time. The novel, thus, prioritizes the stories and tribulations of ordinary people in a highly polarized society that incessantly urge individuals to define their alliances. This article contends that the novel’s representation of the period emphasizes the historical trauma as experienced by the characters rather than presenting a nostalgic glorification of the British or the Irish.
Keywords: J. G. Farrell; Nation; National Identity